2021
DOI: 10.1177/13505076211006543
|View full text |Cite
|
Sign up to set email alerts
|

Academic identities and sense of place: A collaborative autoethnography in the neoliberal university

Abstract: Neoliberalism, precarious jobs, and control of work have multiple effects on academic identities as our allegiances to valued social groups and our connections to meaningful locations are challenged. While identities in neoliberal universities have received increasing research attention, sense of place has passed unnoticed in the literature. We engage with collaborative autoethnography and contribute to the literature in two ways. First, we show that while academic identities are put into motion by the neolibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 79 publications
(152 reference statements)
0
21
0
Order By: Relevance
“…In essence, they constitute an online identity reference from which our participants distance themselves, by highlighting ‘what it is not’ (Carroll and Levy, 2008). Nordbäck et al (2022) had already shown that identities are closely related to both spaces and places. In our case, we saw that dis-identification can also be enacted by physically staying away from specific locations associated with the negative sides of digital nomadism.…”
Section: Discussion: the Role Of Online Archetypes In Identity Workmentioning
confidence: 99%
“…In essence, they constitute an online identity reference from which our participants distance themselves, by highlighting ‘what it is not’ (Carroll and Levy, 2008). Nordbäck et al (2022) had already shown that identities are closely related to both spaces and places. In our case, we saw that dis-identification can also be enacted by physically staying away from specific locations associated with the negative sides of digital nomadism.…”
Section: Discussion: the Role Of Online Archetypes In Identity Workmentioning
confidence: 99%
“…Neoliberalism understood as a political doctrine and form of government that attains to the universalization of social relations through free market (Kallio et al, 2016;Nordbäck et al, 2022) and its impact to public higher education, more specifically UNA, has passed unnoticed for many. While neoliberal practices unarguably is a threat to UNA's social justice mission and values.…”
Section: Successes Limitations and Tensionsmentioning
confidence: 99%
“…We could work on our identities together in our dialogue. Such joint identity work is characteristic of universities today where our work is meticulously controlled and our identities are subject to tensions and struggles (Nordb€ ack et al, 2021).…”
Section: Let's Get Togethermentioning
confidence: 99%
“…During the COVID-19 lockdown in the spring and summer of 2020, wea doctoral researcher and two professorssent texts to each other, taking turns, and followed up on each other's thoughts. We engaged in collaborative autoethnography (Geist-Martin et al, 2010;Chang et al, 2012;Kiriakos and Tienari, 2018;Nordb€ ack et al, 2021) and sought to describe and analyze our lived experiences in order to understand creating ideas as social and cultural experience (Ellis, 2004). One of us suggested that we look into the concept of "etiology," or reflection on how things become as they are, in making sense of how ideas (fail to) catch on.…”
Section: Introductionmentioning
confidence: 99%